2020
DOI: 10.1021/acsinfecdis.0c00108
|View full text |Cite
|
Sign up to set email alerts
|

Effective Strategy Targeting Polymyxin-Resistant Gram-Negative Pathogens: Polymyxin B in Combination with the Selective Serotonin Reuptake Inhibitor Sertraline

Abstract: This study aimed to investigate synergistic antibacterial activity of polymyxin B in combination with the selective serotonin reuptake inhibitor, sertraline, against the Gram-negative pathogens Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa. The combination of polymyxin B and sertraline showed synergistic antibacterial activity in checkerboard and static time-kill assays at clinically relevant concentrations against both polymyxin-susceptible and polymyxin-resistant isolates. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 56 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…The recent trending strategy in testing FDA-approved medications that have no antibacterial activity in combination with antibacterials to enhance the latter’s effect is being applied to polymyxins. In a truly ground-breaking approach, researchers from Australia found that a combination of polymyxin B and the selective serotonin reuptake inhibitor, sertraline, resulted in greater damage to P. aeruginosa , highlighting the likely possibilities of this combination for the treatment of central nervous system infections [ 214 ]. Moreover, the experimental antitumor compound PFK-158 was found to enhance the activity of colistin and delay resistance emergence in mice infected with Enterobacteriaceae [ 215 ].…”
Section: Future Implicationsmentioning
confidence: 99%
“…The recent trending strategy in testing FDA-approved medications that have no antibacterial activity in combination with antibacterials to enhance the latter’s effect is being applied to polymyxins. In a truly ground-breaking approach, researchers from Australia found that a combination of polymyxin B and the selective serotonin reuptake inhibitor, sertraline, resulted in greater damage to P. aeruginosa , highlighting the likely possibilities of this combination for the treatment of central nervous system infections [ 214 ]. Moreover, the experimental antitumor compound PFK-158 was found to enhance the activity of colistin and delay resistance emergence in mice infected with Enterobacteriaceae [ 215 ].…”
Section: Future Implicationsmentioning
confidence: 99%
“…This compound might cause some modifications to the bacterial cellular components which are crucial for synergy as reported for one of the compounds recently [ 45 ]. Additionally, polymyxin and serotonin reuptake inhibitor sertraline combination was shown to affect membrane biogenesis [ 46 ]. The exact mechanism responsible for this synergy obtained with tridecaptin M needs further investigation and is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The primary mechanisms with tamoxifen involve disruption of cell envelope biogenesis and inhibition of lipopolysaccharide (LPS) modifications. In combination with sertraline, polymyxin B impairs glycerophospholipids and fatty acids and the pantothenate and coenzyme A pathways ( 6 , 7 ). These studies may provide valuable information about metabolic pathways leading to an understanding of the adaptations of bacterial strains to antibiotic stress.…”
Section: Introductionmentioning
confidence: 99%